(3GdCfhGQ GdYbdjIs - (3eMeO Hf eMeO Hf eMeO GdZRGdj GdTGaYj GdWhSj , CHh MGeO, MLI GdGSdGe GdZRGdj,J (B505 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi Ybd GdYbd HeTjFI , CeG HYO , aEf Gddg JYGdi deG HOY GdYGde GdQhMGfi hNdb GdYGde GdLSeGfi , ENJGQ GdEfSGf ef SGFQ GdeNdhbGJ s
(3BNQgG (B:s
(3hZQVi ef gPG EfbO GdMGd Ydi Pi GdHUGFQ hGdCSQGQ hCLH UhJgG Yf GdEZjGQ , CYjPc HGddg hChUjc ai Gddg Je cJGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B22 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B266 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B79s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
Keywords: (3GdJUha hGdBOGH GdTQYjIs